Futures Thinking in Middle School Science Textbooks: A Perspective from Japan - Fiel'ardh, Khalifatulloh (Nordic Journal of Comparative and International Education (NJCIE), 2024)
This research aims to illuminate the characteristics of "Futures Thinking" components within the interdisciplinary units of "Science, Technology, and Humanity" and "Nature and Humanity" and "Sustainable development" within Japanese middle school science textbooks. Grounded in pre-existing literatures, this research meticulously organizes the essential competencies of future-oriented thinking into three distinct components: "Envisioning the Future," "Predicting the Future," and "Planning for the Future." Each component is further broken down into more precise indicators. For "Envisioning the Future," indicators include perspectives on "Multiple Futures," the "Science of Future," and "Hope and Fears." For "Predicting the Future," we delve into the "Scenario" technique, alongside "Forecasting" and "Backcasting" strategies. "Planning for the Future" assesses the "Precautionary" approach, "Evaluating Action," and understanding "Risk and Changes." The research involved a cross-sectional analysis of content types (such as texts, diagrams) and contexts (individual, regional, national, and global), determining the presence or absence of these indicators. The findings reveal: (1) a more frequent articulation of these competencies within the "Science, Technology, and Humans" unit, (2) a scant representation of "Multiple Futures" and "Scenario" methods among the nine indicators, (3) a prevalence of explanatory text in presenting these concepts, and (4) a consistent inclination towards a global context in the textbooks' narratives. These insights imply an extant gap within the current pedagogical tools, underscoring the importance of an expanded, multifaceted approach to teaching these competencies. The implications for future curriculum development and instructional strategies in middle school science education are profound, necessitating a more integrated approach that resonates with the uncertainties and possibilities of the future.